A groundwater database for Metro Manila and Laguna Lake Basin - Liongson, Leonardo Q.
A groundwater database for Metro Manila and Laguna Lake Basin has been initiated in 1990 together with an on-going three year research project on the conjunctive maangement and modeling of surface water and groundwater resources in the region. Through a formally organized multi-agency linkage and cooperation, a substantial collection of all agency sourced secondary groundwater and other related data (circa : 1950-present) has been achieved after the first year. The regional database so far consists of 201 technical reports and publications, 234 maps of various types, lithology and other well data for 5911 wells, groundwater level data for 57 observation wells, water quality data for 35 sampling stations,streamflow and lake stage data for 29 surface water stations, climatic data for 17 climate stations, and seismic reflection and georesistivity data for aquifer geometry. Aside from its immediate use in the on-going project, the database has other important long term applications. The database collection and functions are being continually augmented and enhanced in order to realize their long term utility and potential as a source of vital groundwater information for the general user, as management tool for water resources planners and technologists and as generator of research information and studies to be conducted by faculty, researchers, students and practising engineers.